Study of Flood Control Measures for the Melayu and Padolo Rivers in Rasanae Barat District, Bima City - Marisdha Jauhari; Mahendra Andiek Maulana (Journal of Civil Engineering and Planning (JCEP), 2026)
Flooding caused by the overflow of the Padolo and Melayu Rivers in Bima City highlights the need for effective urban flood management. This study aims to analyze flood characteristics, assess flood hazard and risk levels, and evaluate flood control measures in Rasanae Barat District. The analysis employed the Log Pearson Type III (LP III) distribution, the SCS–Snyder Synthetic Unit Hydrograph, and HEC-RAS hydraulic modeling. The results show that the 25-year return period design flood discharge reached 548.04 m³/s for the Padolo River and 174.86 m³/s for the Melayu River, producing an inundation area of 2.224 km² across six urban villages. The highest flood hazard was identified in Dara, Paruga, and Tanjung Villages. Hydraulic simulations indicate that river normalization and levee construction effectively reduce river overflow and flood inundation, demonstrating their potential as effective flood control measures for Bima City.